Perspectives on Obesity and Its Treatment: Health Care Providers and the General Public in Rural West Virginia and Urban Baltimore. (December 2013) - Menez, Steven; Cheskin, Lawrence; Geller, Gail
Objective . To determine and compare the perspectives of the general public and health care providers (HCPs) on obesity and its treatment in rural West Virginia (WV) and Baltimore, MD. Method . Surveys were completed in both locations by the general public (WV: n = 200; Baltimore: n = 171) and HCPs (WV: n = 25; Baltimore: n = 15). Results . BMI (body mass index) ≥ 30 (WV: n = 94; Baltimore: n = 58) was associated with a stronger belief in the heritability of obesity and with the ability to control obesity by controlling food cost, compared with those with normal BMI (WV: n = 42; Baltimore: n = 57). Those with a high school education (WV: n = 112; Baltimore: n = 113) were less likely to agree that obesity is a problem in the community and that proper diet and exercise are realistic expectations, compared with those with at least some higher education. Perspectives of HCPs differed significantly from the general public in both locations. Conclusion . Many differences in perspective on obesity exist between WV and Baltimore, within both populations, and between HCPs and the general public in both settings. A better understanding of patient views is important for effective obesity management. HCPs must consider each patient's level of understanding when discussing management and consequences of obesity. More time spent with patients who have less insight into their obesity may improve patient adherence with treatment and overall patient outcomes.